Полевая мышь (Apodemus agrarius Pall.) в условиях Украины. Сообщение I. Размножение - Свириденко, П.А. (Вестник зоологии, 1971)
The article deals with the results of investigations carried out at the «Alexandria»
reservation (the Belaya Tserkov district, Kiev region).
It was established that the Apodemus agrarius Pall , females became sexually mature weighting not less than 17 g; the pregnancy lasts for 22 days. In one litter there are
from 2 to 10 young ones and for all the years of observations in the reservation — G2 at an
average, the young females have a smaller number of young ones in the litter at an
average and the oldest — the greatest one; there are 3—4 litters a year. The life lime of
A. agrarius under laboratory conditions is up to 1252 days, under natural conditions the
population composition renovates mainly for two years.
The intensity of A. agrarius reproduction in different years is not the same and depends, on weather and fodder conditions in the habitats. Its fecundity in different zones
of the USSR grows from the North to the South, mainly due to an increase in the reproduction period and in a number of litters per year wih a comparatively slight variation
of the brood value.